1945
DOI: 10.6028/jres.034.036
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ilkovic equation to quantitative polarography

Abstract: Conditions of applicability of the Ilkovic equation to polarographic analysis were investigated for representative ions singly and in mixtures. Gelatin was used to suppress maxima found in current-voltage curves.Results obtained with a capillary of usual characteristics showed that a suppresser is necessary to secure agreement with the llkovic equation over any considerable drop-time range, and that the need increases with the drop-rate of the electrode and the dilution of reducible ion. A criterion of diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1947
1947
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The suppression of these maxima is imperative if the absolute method is to be employed. It has been shown that errors of many per cent in the values of diffusion-current constants can result from the presence of maxima which are not readily recognizable (3). Such is the case, for example, when cadmium is electrolyzed in neutral solutions of potassium chloride, where a study of diffusion-current constants as a function of the drop time of the electrode was required to show the presence of maxima.…”
Section: Absolute Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suppression of these maxima is imperative if the absolute method is to be employed. It has been shown that errors of many per cent in the values of diffusion-current constants can result from the presence of maxima which are not readily recognizable (3). Such is the case, for example, when cadmium is electrolyzed in neutral solutions of potassium chloride, where a study of diffusion-current constants as a function of the drop time of the electrode was required to show the presence of maxima.…”
Section: Absolute Methodsmentioning
confidence: 99%
“…If the logarithm of the minimum drop time above which constant values for the diffusion-current constant are obtained, designated as the critical drop time, is plotted with respect to the logarithm of the concentration of gelatin in the solution, a linear relationship is found to exist which is independent of the concentration or nature of the reducible ion. Preliminary experiments have shown that the relationship depends on the size of the drops produced by the electrode, but the quantitative relationship has not been determined as yet (3).…”
Section: Absolute Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr(0H)(H20)5 + + + 3e = Cr + 5H20 + OH' (13) as well as by the reversal of the hydrolytic equilibrium 10 in the diffusion layer, there would be no contribution at all of hydrogen ion to the total diffusion current if Dc, were equal to Dh. The observed hydrolysis current results from the fact that the diffusion coefficient of hydrogen ion actually is much larger than that of the hydrolyzed chromic ion.…”
Section: Theory Limiting Currents Controlled By Reaction Ratesmentioning
confidence: 99%
“…One solution was 0.45 millimolar in cadmium, 1 " in hydrochloric acid, and contained 0.01% gelatin to suppress maxima. The other solution contained the same amount of cadmium and gelatin but was 1 ,V in nitric acid.…”
Section: Examplesmentioning
confidence: 99%